Difficulties Faced by the Undergraduate Medical Students in Relation to Institution and Hostel Campus: Views of Selected Medical Colleges of Bangladesh (Bangladesh Journal of Medical Education, 2019)
This study set out to identify the institutional difficulties encountered by the undergraduate medical students of Bangladesh. This was a descriptive type of cross sectional study, conducted from July 2017 to June 2018. The population of the study consisted of undergraduate medical students and medical teachers of 8 medical colleges of Bangladesh including both government and non-government which were located in Dhaka and outside of the Dhaka. Medical colleges and medical teachers were selected purposively and students were selected by the convenience sampling technique. The questionnaire using five points Likert scale were administered on 1059 medical students and in-depth interviews were conducted with 13 medical teachers. The study revealed that most of the students faced institutional related difficulties, particularly cleanliness of campus 480 (45.6%), unclean toilet 762 (72%), poor quality canteen 663 (63%), poor games facilities 792 (75%), insufficient hostel accommodation 669 (65.2%), unclean hostel 652 (63.5%), insufficient recreation facilities in hostel 702 (68.5%) and irregular hostel supervision by the authority 590 (57.6%). Based on the study, it was suggested that concerned authority should consider the findings and should take some significant steps for sustainable solutions to the difficulties of the students.Bangladesh Journal of Medical Education Vol.10(2) 2019: 23-25